Summer fast ice evolution off Zhongshan Station, Antarctica - Ruibo, Lei; Zhijun, Li; Zhanhai, Zhang; Yangfeng, Cheng; Yinke, Dou (Polar Research Institute of China - PRIC, 2008)
Based on the field data acquired in the program of fast ice observation off Zhongshan Station, Prydz Bay, East Antarctica during the austral summer 2005/2006, physical properties evolution of fast ice during the ice ablation season is analyzed in detail. Results show that the annual maximum ice thickness in 2005 occurred in later November, and then ice started to melt, and the ablation duration was 62 days; sea water under the ice became warmer synchronously; corresponding to the warming sea ice temperature, a "relative cold mid-layer" appeared in sea ice; the fast ice marginal line recoiled back to the shore observably, and the recoil distance was 20.9 km from 18 December 2005 through 14 January 2006. In addition, based on the data of sea ice thickness survey along the investigation course of MV Xuelong on December 18 of 2005, the ice thickness distribution paten in the marginal ice zone have been described: sea ice thickness increased, but the diversity of floe ice thickness decreased from open water to fast ice zone distinctly.